Answer :

Let

Then tan x = 1 =


……(i)


Let


Then cos y =


……(ii)


Again,


Let


Then sin z =


……(iii)


Now,



= [from (i), (ii), (iii)]


=


=


=


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove the followiMathematics - Board Papers

Solve the followiMathematics - Board Papers